Kajian Kelembagaan dan Peran Strategis Bank Sentral dalam Rencana Redemonisasi Rupiah - Rayhan Wahyu Dwi Putra; Muhamad Hanidar Dafa Amanullah; Melinda Ayu Andani; Desmitha Rachel Suyyina; Rahadyan Wegig Priyambodo (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the readiness and role of Bank Indonesia in designing and implementing the redenomination policy, while also assessing its potential impact on improving the efficiency of the national monetary system. Using a literature review method that includes academic journals, books, official reports, and previous research, the findings indicate that the success of redenomination is strongly influenced by macroeconomic stability, policy coordination between the central bank and the government, technological preparedness within the payment system, and the public’s understanding of the transition to the new nominal structure. The analysis reveals that redenomination may simplify financial transactions, reduce operational costs in currency management, accelerate data-processing activities, and strengthen the credibility of the national currency among the public and investors. However, challenges such as public misconceptions about redenomination, potential confusion during the transition period, and the need for political legitimacy from the legislature must be addressed through comprehensive public outreach and strong regulatory support. Overall, this study concludes that redenomination can significantly enhance monetary efficiency when implemented carefully, supported by stable economic conditions, well-coordinated institutions, and active engagement from all stakeholders.